2016
DOI: 10.4103/0975-7406.199335
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for developing drug-related problems in patients with cardiovascular diseases attending Gondar University Hospital, Ethiopia

Abstract: Background:Cardiovascular diseases (CVDs) are often accompanied with comoribidities and complications leading to taking multiple drugs and thus are more liable to be exposed to drug-related problems (DRPs). DRPs can occur at any stages of medication process from prescription to follow-up treatment. However, a few studies have assessed the specific risk factors for occurrence of at least one potential DRP per patient with CVDs in sub-Saharan African region.Aim:We aim to assess the risk factors for developing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
5
12
0
1
Order By: Relevance
“…This study is one of the first research to have determined the factors associated with the occurrence of DTPs at the primary care level (24), by employing the theoretical framework proposed by Cipolle et al Moreover, it appears to be the first study to have established DTP-associated factors among general ambulatory patients, by using the aforementioned methodology. In line with published evidence (24,28,29), polymedicated patients were more likely to have a higher number of DTPs. The second characteristic most strongly associated with the occurrence of three or more DTPs was type 2 diabetes.…”
Section: Quantitative Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This study is one of the first research to have determined the factors associated with the occurrence of DTPs at the primary care level (24), by employing the theoretical framework proposed by Cipolle et al Moreover, it appears to be the first study to have established DTP-associated factors among general ambulatory patients, by using the aforementioned methodology. In line with published evidence (24,28,29), polymedicated patients were more likely to have a higher number of DTPs. The second characteristic most strongly associated with the occurrence of three or more DTPs was type 2 diabetes.…”
Section: Quantitative Resultssupporting
confidence: 86%
“…In addition, various studies have demonstrated its effectiveness on clinical (14,15,(17)(18)(19)(20)(21)(22)(23)(24), economic (17,22,23,25) and humanistic outcomes (26,27). Other studies determined some factors associated with the occurrence of DTPs, such as polypharmacy, multimorbidity and age, yet employed methodology or clinical settings dissimilar to the present study (28)(29)(30)(31). However, to the best of authors' knowledge, until now, no study determined the associated factors of patients with chronic diseases at the primary care level as they receive CMM services that follow the theoretical framework proposed by Cipolle et al (9).…”
mentioning
confidence: 93%
“…Currently, little is known about risk factors for the development of DRP in the average patient in a general hospital. Risk factors for DRP have been specifically studied in elderly populations [23], patients from medical specialties such as cardiology [24,25] and paediatrics [26]. To the best of our knowledge, there has been a single report in the literature investigating risk factors and developing a risk score for DRP in adult patients at hospital admission in general wards, the study by Urbina et al [13], with a subsequent validation study by Ferrández et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…The hospital provides fee waiver for maternal care related services. The hospital has a more than 1000-bed capacity and provides service to over 200,000 patients annually [ 23 ]. The hospital serves as a referral center for four district hospitals in the area [ 24 ].…”
Section: Methodsmentioning
confidence: 99%